Evaluation of a tailored training programme to improve the assessment and treatment of trauma in an Early Intervention in Psychosis (EIP) service. Issue 3 (2nd July 2016) - Walters, Sasha; Hogg, Lorna; Gillmore, Chris
Abstract : The correlation of psychosis and the experience of traumatic events is widely recognised in the literature and by NICE guidelines. Research suggests that around two-thirds of patients are not asked about trauma, and guidance for treatment is limited. The aim of the current study was to improve adherence to evidence-based practice by identifying, and reducing, barriers to the assessment and treatment of complex trauma in early intervention (EI) patients. The Plan Do Study Act model of service improvement was employed to guide the intervention delivered to an EI staff team. This included completing a focus group to identify staff needs and the development and delivery of a training programme which met these needs. A questionnaire was developed to assess the impact of the intervention at reducing barriers to assessing and treating trauma. The training package significantly improved staff members' confidence and knowledge in assessing and treating trauma, and marginally reduced worries. Improvement was maintained after 6 months of implementing skills despite team restructuring. Consideration of the impact for service users, relevance of this intervention for similar services and directions for future progression are discussed.